2020
DOI: 10.1002/slct.202001013
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Anti‐Proliferative Activity of a Triazole‐Fused Thymidine Analogue

Abstract: Here we report the synthesis of two-an acyclic and a macrocyclic-analogues of thymidine linked to a triazole moiety. The new molecules were synthesized through an intramolecular 1,3-dipolar cycloaddition reaction of the diazido derivative of thymidine with a suitable alkyne. The acyclic nucleoside showed dose dependent cytotoxicity against glioblastoma and breast cancer cells by causing significant cellular damage as studied with confocal laser scanning microscopy. In silico induced fit molecular docking studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Rahman et al, in 2020, developed a thymidine analogue with linked triazoles 235 and tested its anti-proliferative activities (Scheme 25). 32 Commercially available thymidine 232 was initially converted into its di-azide derivative 233 in three sequential steps and subsequently exposed to CuAAC reaction with 1,3-diethynyl benzene 234 using a CuI/DIPEA system in acetonitrile for 36 h to afford the macrocyclic thymidine analogue 235 (56%). Biological assessment showed that 235 expressed significant toxicity when tested against C6 glioblastoma cancer cell lines, MCF7…”
Section: Scheme 24 Synthesis Of Triazole-fused Macrocycle 231mentioning
confidence: 99%
“…Rahman et al, in 2020, developed a thymidine analogue with linked triazoles 235 and tested its anti-proliferative activities (Scheme 25). 32 Commercially available thymidine 232 was initially converted into its di-azide derivative 233 in three sequential steps and subsequently exposed to CuAAC reaction with 1,3-diethynyl benzene 234 using a CuI/DIPEA system in acetonitrile for 36 h to afford the macrocyclic thymidine analogue 235 (56%). Biological assessment showed that 235 expressed significant toxicity when tested against C6 glioblastoma cancer cell lines, MCF7…”
Section: Scheme 24 Synthesis Of Triazole-fused Macrocycle 231mentioning
confidence: 99%
“…Rahman et al, in 2020, developed a thymidine analogue with linked triazoles 235 and tested its anti-proliferative activities (Scheme 25). 32 Commercially available thymidine 232 was initially converted into its di-azide derivative 233 in three sequential steps and consecutively exposed to CuAAC reaction with 1,3-diethynyl benzene 234 using a CuI/DIPEA system in acetonitrile for 36 h in order to afford the macrocyclic thymidine analogue 235 (56%). Biological assessment showed that 235 expressed significant toxicity when tested against C6 glioblastoma cancer cell lines, MCF7 breast cancer cell lines and HT29 colorectal adenocarcinoma cell lines.…”
Section: Scheme 23 Synthesis Of Triazole Fused Macrocycle 223mentioning
confidence: 99%
“…1,2,3‐Triazole‐dihydropyrimidinone hybrids 52 (GI 50 : 24–38 µM, SRB assay) and the bis‐1,2,3‐triazole‐dihydropyrimidinone analogs 53 (GI 50 : 37–77 µM) exhibited moderate antiproliferative activity against HBL‐100 and T‐47D breast cancer cell lines, [ 80 ] whereas bis‐1,2,3‐triazole‐thymidine derivative 54 (IC 50 : 1.0 µM) possessed promising antiproliferative activity against MCF‐7 breast cancer cells. [ 81 ] Hence, hybrid 54 could serve as a lead compound for the further structural modifications.…”
Section: 23‐triazole‐pyrimidine/quinazoline Hybridsmentioning
confidence: 99%